DEPRESSION, ANXIETY AND MYOCARDIAL INFARCTION: EVERYTHING JUST BEGINS (PART I) - Y. A. Vasyuk; A. V. Lebedev (Столичная издательская компания, 2015)
A review is devoted to a comorbidity of myocardial infarction and anxious and depressive disorders. In the first part data concerning prevalence of depression in myocardial infarction, pathophysiological mechanisms connecting depression and ischemic heart disease (IHD) are given. Influence of concomitant depressive disorders on clinical state and forecast of patients after myocardial infarction is discussed. The second part of the review (Rational Pharmacother. Cardiol. 2007, 4) will be devoted to the anxious disorders in myocardial infarction as well as to influence of anxious and depressive disorders on life quality of patients with myocardial infarction. Besides, contemporary approaches to the therapy of anxious and depressive disorders in patients with IHD will be discussed.